(untitled) (Periphērica, 2019)
Book review of Theatre and Cartographies of Power Repositioning the Latina/o Americas, an anthology of essays on Latin American and Latinx theatre-making. Edited by Analola Santana and Jimmy A. Noriega. Southern Illinois University Press, 2018.